Effect of Compression Ratio on Performance and Emission Characteristics of Dual Spark Plug Ignition Engine Fueled With n-Butanol as Additive Fuel - Ravikumar Ramegouda; Antony Alappath Joseph (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Renewable energy called normal-butanol is a possible alternative fuel for automobile vehicles like some other possible fuel such as compressed natural gas (CNG), liquid petroleum gas (LPG), ethanol, and methanol. Bio-butanol or normal-butanol is also a meritable energy source to substitute for regular fossil fuels. The normal-butanol has recently started to use as a possible substitute fuel to regular fuels for internal combustion engines to attain eco-friendly and capital benefits. As compared to regular energy sources in internal combustion engines, normal-butanol has some benefits, so it shows the potential to decrease tailpipe emission andan increase in positive network delivery. The current work carried out to investigate the performance and emission characteristics of dual spark plug ignition engine fuelled with normal-butanol as additive fuel by adopting 10:1 and 10.5:1compression ratios. The experimental results reveal that when compared between 10:1 and 10.5:1 compression ratios, brake power (BP) is increased by 3.5% and 3.2% for normal-Butanol 35 (nB35) blend and energy efficiency increased by 2.72% and 2.14% for nB35 blend at a part and full load for 10.5:1 compression ratio. The n-butanol create a greater impact on tailpipe emissions that the carbon monoxide (CO) decreased by 32%, 29%, and hydrocarbon (HC) reduced by 2.38% and 2.22% for nB35 blend at a part and full load condition respectively. The experimental results on dual spark ignition engine using n-butanol as additive fuel by varying compression ratioreveals that n-butanol can be a suitable replacement energy source for the automobile sector in the nearest future.